Efektivitas ekstrak daging buah pala (Myristica fragrans Houtt) terhadap histopatologi hati pada tikus hiperglikemia - Amran Nur; Safitri Hasda Nur; Nur Asma S. Somadayo; Muhammad Fakhrur Rajih (Poltekkes Kemenkes Aceh, 2024)
Background: Hyperglycemia can occur due to insulin resistance, which affects the metabolism of lipids, carbohydrates, proteins, and fatty acids in the liver, which will ultimately cause cirrhosis, steatohepatitis, liver cancer, and other liver disorders.Objectives: To determine the effect of administering nutmeg pulp extract (Myristica fragrans H.) on the histopathological picture of the liver of hyperglycemic mice induced by high carbohydrate feed.Methods: The research was carried out using an experimental method using 25 white rats (Rattus norvegicus) of the Wistar strain, which were divided into five groups, K- (NaCMC 1%), K+ (Metformin), P1-P3 respectively Nutmeg extract 100mg/kgBW, 200mg/kgBB, 300mg/kgBB). The entire group was given high carbohydrate feed for 30 days, then extract and Metformin for seven days. On the 36th day, the liver was removed, and histopathology preparations were made. The main research outcome parameters include initial blood sugar levels before induction (T0), final day blood sugar levels (T30), blood sugar levels on days 1, 3, 5, and 7 after sample administration, liver weight, and liver severity score. The data obtained were analyzed using Oneway-Anova with a significance of 0.05, and LSD as a further testResults: The K+, P1, and P3 groups showed a significant reduction in sugar compared to the control group (p<0.05), but all groups did not show an improvement in liver histopathology with damage scores in the mild to severe damage category.Conclusion: Nutmeg pulp extract at doses of 100mg/kgBB, 200mg/kgBB, and 300mg/kgBB showed effectiveness in reducing blood sugar in hyperglycemic white mice but could not show optimal improvement in liver cell damage.Keywords:Diabetes mellitus, Histopatology, Liver, Myristica fragrans, Nutmeg Flesh.